TREATMENT OPTIONS FOR COVID-19 WITH VITAMIN D SUPPLEMENTS - Tetiana V. Fartushok; Nadiia V. Fartushok; Serhii Z. Baran (Клінічна та профілактична медицина)
Introduction. Recently, the study of the relationship between vitamin D deficiency and adequate immune response has been of particular interest, particularly in the context of the COVID-19 pandemic and its impact on disease prognosis. Confirmation that vitamin D affects the functioning of the immune system was the detection of calcitriol receptors in cells of the immune system, as well as the ability of mononuclear phagocytes to produce 1,25(OH)2D3. The increase in the expression of antimicrobial peptides by immunocytes with the participation of vitamin D is accompanied by the simultaneous suppression of the production of pro-inflammatory cytokines interleukin-1β (IL-1β), IL-12 and tumour necrosis factor-α. Vitamin D also inhibits the proliferation of B-lymphocytes, their differentiation into plasma cells and the production of immunoglobulins, promotes the induction of regulatory T cells, which leads to a decrease in the production of pro-inflammatory cytokines (IL-17, IL-21) and an increase in the production of anti-inflammatory cytokines (IL-10). The anti-inflammatory role of vitamin D explains its protective properties in the event of immune hyperreactivity and "cytokine storm" in a subgroup of patients with a severe course of COVID-19.Aim. To analyze the role of vitamin D in the prevention of COVID-19. Materials and methods. Thirty thrеe articles were analyzed using the following Keywords: phosphorus-calcium metabolism, immune system, COVID-19, and vitamin D. A review of the available literature was conducted through PubMed, the National Library of Medicine, and Medscape.